Transmitting intangible cultural heritage through ethnomusicology coursework : cases from Sabah, Malaysia - Jacqueline Pugh-Kitingan (2017)
The UNESCO 2003 Convention for the Safeguarding of the Intangible Cultural Heritage includes but does not define practices and expressions such as music, dance, oratory, ritual, and the objects and spaces associated therewith. It states that this heritage is passed on ‘from generation to generation’ and that it is ‘constantly recreated by communities and groups in response to their environment, interaction with nature and history, and it provides them with a sense of identity and continuity’